O Brasil como Brasiliana: uma biblioteca portuguesa e sua “república luso-brasileira das letras” em meados do século xx - Débora Dias (Les Cahiers de Framespa)
Portugal’s interest in Brazil advanced in the first half of the 20th century and was not restricted to large collectors and to rare and more bibliophilic editions. This article aims to understand the context and formation of Brasiliana libraries, whether private or official, sent from Brazil to Portugal. In more vertical fashion, the analysis will cover the modes of selection, acquisition, and shipping of Brazilian books to the personal Brasiliana of Joaquim de Carvalho (1892-1958), a professor and former director of the Coimbra University Press, until it was closed by Salazar (1934). Based on epistolary sources and the very materiality of the books, we accompany the modes of cultural reception and observe the existence of a heterogeneous communicative web of university students, scholars, editors, and booksellers, which furthermore demonstrates its contours as an alternative to the official exchange between the two countries while posing the fundamental question: “what must one read to know Brazil?”.